Desgaste de dressadores de ponta única fabricados com diamantes cvd nacionais - Frech Jr., A. [UNESP]; Bianchi, E. C. [UNESP]; Canarim, R. C. [UNESP]; Aguiar, P. R. [UNESP] (Associação Brasileira de Cerâmica, 2013)
This study attempted to observe the performance of three types of diamonds, two natural and one synthetic, to determine which features longer life and greater wear than the others. The methodology employed in this study was to dressed an aluminum oxide grinding wheel, and every twenty paces with a advance of depth dressing of 40 µm per passes, take an image of the tip in a horizontal position and the other in the vertical position of this diamond in a stereoscopic. Thereafter, the dresser was replaced in the rectifier to conduct a new dressing. The criteria to completion of the test was the spark generated by the grinding wheel contact with the base of the dresser, which indicates the end of the contact with the diamond wheel. After the tests, was calculated the areas worn of each diamond in accordance with each image obtained through the aid of a graphics software. The data were then arranged in graphs.

Neste trabalho, buscou-se observar a atuação de três tipos de diamantes, dois naturais e um sintético, para determinar qual deles apresenta vida útil maior ou com maior desgaste em relação aos demais. A metodologia empregada nesse estudo foi o de dressar um rebolo de óxido de alumínio e, a cada vinte passadas com um avanço da profundidade de dressagem de 40 µm por passada, tirar uma imagem da ponta na posição horizontal e outra na posição vertical deste diamante num microscópio estereoscópio. Após isso, o dressador foi recolocado na retificadora para a realização de uma nova dressagem. O critério para o fim do ensaio foi o faiscamento, gerado pelo contato do rebolo com a base do dressador, que indicou o fim do contato do diamante com o rebolo. Após os ensaios, foram calculadas as áreas gastas de cada diamante de acordo com cada imagem obtida por meio do auxilio de um software gráfico. Os dados foram então dispostos em gráficos.
Single point wear dressers manufactured with national cvd diamonds
Keywords: dressagem; retificação; desgaste do dressador; dressing; grinding; wear dresser